1991
DOI: 10.1172/jci115338
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression and function of VLA-4 fibronectin receptors on human activated T cells in rheumatoid arthritis.

Abstract: The VLA4 (CD49d/CD29) integrin is a cell surface receptor involved in the interaction of lymphoid cells with both extracellular matrix (ECM) and endothelial cells. We have investigated the expression and function of VLA4 fibronectin (FN) receptors on T cells localized in the inflammed synovium of patients with rheumatoid arthritis (RA). A high proportion of T cells in both synovial membrane (SM) and synovial fluid (SF) expressed the activation antigens AIM (CD69) and gp95/85 (Ea2) as well as an increased numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
0
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(117 citation statements)
references
References 50 publications
(38 reference statements)
9
106
0
2
Order By: Relevance
“…Of relevance is the reported observation that in serial synovial biopsies from patients who responded to gold salt therapy with a clinical reduction in joint inflammation, there was reduced expression of ELAM-1, but no change in the mononuclear cell infiltrate in the membrane (31). We (19) and others (32) have also shown that lymphocytes and macrophages in rheumatoid synovial tissues appear to express high levels of the PI-integrin VLA-4, the known leukocyte receptor for VCAM-1. A study measuring the adherence of lymphocytes to frozen sections of rheumatoid synovial tissue has indicated that VLA-WVCAM-1 interactions appear to be of primary importance in lymphocyte homing to rheumatoid synovium (33).…”
Section: Discussionsupporting
confidence: 54%
“…Of relevance is the reported observation that in serial synovial biopsies from patients who responded to gold salt therapy with a clinical reduction in joint inflammation, there was reduced expression of ELAM-1, but no change in the mononuclear cell infiltrate in the membrane (31). We (19) and others (32) have also shown that lymphocytes and macrophages in rheumatoid synovial tissues appear to express high levels of the PI-integrin VLA-4, the known leukocyte receptor for VCAM-1. A study measuring the adherence of lymphocytes to frozen sections of rheumatoid synovial tissue has indicated that VLA-WVCAM-1 interactions appear to be of primary importance in lymphocyte homing to rheumatoid synovium (33).…”
Section: Discussionsupporting
confidence: 54%
“…n Ն 6 mice for each genotype. arthritis patients (69), and strikingly, these included an unusual CD69 ϩ /CD25 Ϫ T cell subset (70). CD4 T cell activation was apparent in the youngest animals examined (6 wk) and did not show a significant increase as the mice aged up to 12 wk.…”
Section: T Cell Activation In Lpr/lpr Micementioning
confidence: 92%
“…T lymphocytes derived from RA synovial tissue display markers of recent activation, including up-regulation of HLA class II proteins and very late activation antigen 4 integrins (4,5). Consistent with this activated phenotype, RA synovial T lymphocytes can stimulate monocyte tumor necrosis factor ␣ (TNF␣) production in a cell-cell-dependent manner (6).…”
Section: Synovial Adherent Cells and This Correlated With T Cell Mitmentioning
confidence: 97%